Logic and theism : arguments for and against beliefs in God - Sobel, Jordan Howard (Cambridge ; New York : Cambridge University Press, 2004)
This is a wide-ranging book about arguments for and against beliefs in God. This book will be a valuable resource for philosophers of religion and theologians and will interest logicians and mathematicians as well.
Cover; Half-title; Title; Copyright; Dedication; Contents; Preface; DIVINITY; I 'God', 'god', and God; ARGUMENTS FOR THE EXISTENCE OF GOD; II Classical Ontological Arguments; III Modern Modal Ontological Arguments; IV Kurt Godel's Ontologischer Beweis; v First Causes; VI Ultimate Reasons; VII Look 'Round; VIII Clouds of Witnesses; ON TWO PARTS OF THE COMMON CONCEPTION; IX Romancing the Stone; X 'God Knows (Go Figure)'; ARGUMENTS AGAINST THE EXISTENCE OF GOD; XI Atheologies, Demonstrative and Evidential; XII The Logical Problem of Evil; PRACTICAL ARGUMENTS FOR AND AGAINST THEISTIC BELIEFS.
Includes bibliographical references (pages 630-646) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: God -- Proof; Logic; Dieu -- Existence; RELIGION -- General; God -- Proof; Godsbewijzen; Theïsme.; Logica; Gottesbeweis; Atheismus; Electronic books